ALOKASI WAKTU DAN PENDAPATAN PETANI DALAM KEGIATAN KELOMPOK WANITA TANI SELAKASO DI KELURAHAN CIBEUREUM, KECAMATAN LEMBURSITU, KABUPATEN SUKABUMI - Eneng Nurlatifah munggaran; Endang Tri Astutiningsih; Reny Sukmawani (Fakultas Pertanian Universitas Majalengka, 2021)
The Selakaso Women Farmers Group is a forum that provides opportunities for women to participate in advancing the agricultural sector. The Women Farmers Group has three roles, namely as a vehicle for learning, a vehicle for cooperation and production which is implemented by KWT Selakaso in counseling activities, gymnastics and production units. This study aims to determine the impact of farmers' time allocation in the activities of the Selakaso Women's Farmer Group on farmers' income. This study uses an explanatory method and a quantitative approach. Based on the results of the analysis that has been carried out in this study, it was found that the income of farmers from KWT Selakaso was significantly influenced by the time allocation of farmers in extension activities and the allocation of farmers' time in production activities. But it is not significantly affected by the time allocation in gymnastics or collaboration activities. So it is necessary to increase the time allocation by establishing partnerships between farmer groups and outside parties.